Modulation of inflammatory responses by gastrointestinal Prevotella spp. - From associations to functional studies - Aida Iljazovic; Lena Amend; Eric J.C. Galvez; Romulo de Oliveira; Till Strowig (Elsevier, 2021)
Numerous studies have associated alterations in the gut microbiota composition with almost every known inflammatory disease. However, proving the biological relevance of distinct microbial signatures and linking specific microorganisms to host phenotypes, remains a considerable challenge. Correspondingly, increased abundance of members of Prevotella genus within microbial communities colonizing distinct mucosal surfaces has been found in individuals diagnosed with rheumatoid arthritis, periodontitis, metabolic disorders, and intestinal and vaginal dysbiosis. Still, the role of Prevotella spp. in the incidence of these diseases continues to be debated. For many years, poor understanding of Prevotella biology could be in large part attributed to the lack of experimental tools. However, in the recent years significant advances have been made towards overcoming these limitations, including increased number of isolates and improved understanding of genetic diversity. Besides discussing the most relevant associations between Prevotella spp. and inflammatory disorders, in the present review we examine the recent efforts to expand the Prevotella experimental "toolbox" and we highlight remaining experimental challenges that should advance future research and our understanding of Prevotella-host interplay.